Physiological Responses of Pocillopora acuta and Porites lutea Under Plastic and Fishing Net Stress - Ying, Long; Sinutok, Sutinee; Pramneechote, Pathompong; Aiyarak, Pattara; Ralph, Peter J.; Chotikarn, Ponlachart (Frontiers in Marine Science, 2021)
Marine debris has become a global problem affecting coral health around the globe. However, the photophysiological responses of corals to marine debris stress remain unclear. Therefore, this study firstly investigated transparent and opaque plastic bag shading and fishing nets directly contacting the coral. Photosynthetic performance, pigment content, symbiont density, and calcification rate of a branching coral Pocillopora acuta and a massive coral Porites lutea were investigated after 4 weeks of exposure to marine debris. The results show that the maximum quantum yield of PSII significantly decreased in P. lutea with all treatments, while P. acuta showed no effect on the maximum quantum yield of PSII from any treatments. Transparent plastic bag shading does not affect P. acuta, but significantly affected the maximum photochemical efficiency of P. lutea. Photoacclimation of cellular pigment content was also observed under opaque plastic bag shading for both species at week 2. Fishing nets had the strongest effect and resulted in P. acuta bleaching and P. lutea partial mortality as well as a decline in zooxanthellae density. Calcification rate of P. acuta significantly decreased with treatments using opaque plastic bag and fishing net, but for P. lutea only the treatment with fishing net gave any observable effects. This study suggests that the sensitivities of corals to marine debris differ strongly by species and morphology of the coral.